Iran Diabetes Research Roadmap (IDRR) Study; Research Gap in Gestational Diabetes in Iran: A Review Article - Camelia RAMBOD; Gita SHAFIEE; Fatemeh BANDARIAN; Bagher LARIJANI; Farideh RAZI (Tehran University of Medical Sciences, 2017)
Background: Gestational diabetes mellitus has adverse effects on maternal and fetal outcomes during pregnancy and after delivery. The aim of this study was evaluation of the status of scientific research in gestational diabetes mellitus (GDM) in Iran. Methods: This study is a part of the Iranian diabetes research roadmap (IDDR) project. We investigated the electronic database, including PubMed, Web of Science and Scopus as well as Scientific Information Database (SID), Indexing Articles Published in Iran Biomedical Journals (Iran Medex) and Iranian Magazine Database (Magiran) and extracted documents published by Iranian authors up to 2015. We also determined the subject area and the study design as well as the WHO and Australian National Health classifications. Results: There were 229 relevant publications related to GDM. The most rapidly increasing trend in the publication was observed in two stages; 2007-2009 and then 2010-2013. The highest portion of the publications was clinical studies (74%). Regarding the study design, cross-sectional (32%), case-control (26%) and cohort (18%) studies were the most common types of studies. Regarding the subject, the most percentage of publications were allocated to fetal complications (46%) and the least were about prevention of GDM (1%). Conclusion: The research about the GDM is non-coordinated and not effective and there is not any participated framework to guide the research related to GDM in Iran. Thus, it is critical to provide the roadmap for GDM studies to preserve time and money. This study identified and highlighted the research gap in GDM in Iran to provide a roadmap for the medical research of GDM.